The Japanese way of justice : prosecuting crime in Japan - Johnson, David T. (David Ted), 1960- (Studies on law and social control., 2002)
In the Japanese criminal system, the prosecutor is the most important figure. Based on extensive fieldwork inside a large prosecutor's office and on extensive surveys and interviews, this book explains the role of Japan's 2000 prosecutors.